2017
DOI: 10.1038/srep41933
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Mass Index with the Tuberculosis Infection: a Population-based Study among 17796 Adults in Rural China

Abstract: Body mass index (BMI) has been shown to be associated with host susceptibility to several infections. However, the link between BMI and the risk of tuberculosis (TB) infection has been sparsely studied in China and in worldwide. Based on the baseline survey of a population-based, prospective study in rural China, the association between BMI and TB infection among adults was estimated by means of cross-sectional analysis. TB infection status was tested using QuantiFERON-TB Gold In-Tube (QFT), a commercial of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 21 publications
5
29
0
Order By: Relevance
“…Our result is consistent with a recent report that in those cases without cavitation, the radiological severity of disease on chest X-ray prior to treatment in smear-positive pulmonary TB patients has no association with the bacterial burden [ 40 ]. It may therefore explain the seemingly paradox association of BMI [ 41 43 ] and anti-TB antibody [ 26 , 44 , 45 ] response with the bacterial counts and cavity in TB patients, in our data and previous reports.…”
Section: Discussionsupporting
confidence: 66%
“…Our result is consistent with a recent report that in those cases without cavitation, the radiological severity of disease on chest X-ray prior to treatment in smear-positive pulmonary TB patients has no association with the bacterial burden [ 40 ]. It may therefore explain the seemingly paradox association of BMI [ 41 43 ] and anti-TB antibody [ 26 , 44 , 45 ] response with the bacterial counts and cavity in TB patients, in our data and previous reports.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, adipose tissue participates in inflammation and immunity, producing and releasing a variety of pro-inflammatory and anti-inflammatory factors that might influence susceptibility to infections [ 7 ]. In one study, BMI above 28 kg/m 2 was independently associated with host susceptibility of TB in rural China [ 8 ]. Additionally, although an inverse logarithmic relationship between TB incidence and BMI was showed in another study, the relationship was uncertain at a BMI above 30 kg/m 2 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…22 However, this study contradicts findings reported from US, 23 UK 24 and China. 25 Variations among studies could be attributable to differences in sample size, study settings, follow-up periods, and sociodemographic characteristics of study participants. Furthermore, one of the most significant predictors of TB among diabetic patients was a history of TB.…”
Section: Discussionmentioning
confidence: 99%